Effects of exercise on chromium levels. Is supplementation required? - Clarkson, P. M. (Sports Medicine, 1997)
It is estimated that most individuals are not ingesting sufficient amounts of chromium in their diets. Although there is little information on chromium intake in athletes, many athletes ingest more calories than do non-athletes so their chromium intake should be adequate. However, athletes who restrict calories to maintain low bodyweights could compromise their chromium status. Some evidence also shows that exercise may increase chromium loss into the urine. At present, it is not known whether this loss necessitates additional chromium in the diet or whether the body will increase retention in response to the loss. Chromium deficiency is thought to contribute to glucose intolerance and unhealthy blood lipid profiles. The primary function of chromium is to potentiate the effects of insulin, and thereby alter glucose, amino acid and fat metabolism. Chromium supplements have been purported to increase muscle mass and decrease body fat. However, the preponderance of evidence has not supported this claim. There is little information available on the long term use of chromium supplements, but at present, supplements within the Estimated Safe and Adequate Daily Dietary Allowance (ESADDI) level do not appear harmful. The prudent course of action for athletes would be to ingest foods rich in chromium and perhaps take a multivitamin/mineral supplement containing no more than the ESADDI of chromium.